Unified Failure Strength Criterion for Terrace Slope Reinforcement Materials - Xuan Fang; Jie Yang; Jia-Ming Na; Zhen-Yuan Gu (Advances in Civil Engineering)
This paper presents a study on the failure strength criterion of terrace slope reinforcement materials, such as lean cemented sand and gravel (LCSG) material, under a triaxial stress state. Cement content and confining pressure were selected as major factors to investigate their influence on the peak stress of terrace slope reinforcement materials based on experimental results and data from the literature. The mechanical properties of the LCSG samples, with cement contents of 60, 80, and 90 kg/m3, and noncemented sand and gravel materials were tested under four confining pressure levels (namely, 300, 600, 1000, and 1500 kPa). The results show that the strength of LCSG material improves as the confining pressure increases. When the confining pressure exceeds 1200 kPa, the rate of increase of the strength for LCSG material and other cemented grained materials declines generally. The material strength displays a linear increase with the growth of the cement content. When the axial load rises up to a certain value, damage will occur at the particle cemented site near the shear plane, and the resistance stress generated by the cementation shows a trend of growth first and then attenuation, and concurrently, the friction between particles increases by degrees. Based on the identified strength characteristics of LCSG material under different cement contents and confining pressures, a new strength criterion that incorporates the frictional strengths and the cementing strengths is proposed for LCSG and other similar materials. The results of this work can provide an important theoretical basis for the stability calculation of terrace slopes and LCSG dams.